P193 Both the standard and a modified capsule endoscopy Lewis score of inflammation correlates with faecal calprotectin and small bowel tranit time. (16th January 2018) - Barnes, A; Bond, A; Skouras, T; Collins, P
Abstract: Background: Small bowel video capsule endoscopy (VCE) is an established tool for the non-invasive examination of the small bowel mucosa. It is a useful adjunct for the assessment of small bowel inflammation in patients with suspected or established Crohn's disease. The Lewis score (LS) is a validated semi-quantitative system used to assess the burden of small bowel inflammation seen at VCE. 1 The score is calculated by adding the score for the most severely inflamed tertile (villous oedema and ulceration) to a score for any stenosis in the small bowel. A modified Lewis Score (mLS) incorporating a summation of scores for all three small bowel tertiles has been suggested as being more representative of the burden of inflammation. 2 Previous studies have suggested that inflammation may affect the speed of small bowel transit. Hypotheses: 1. Biological markers of inflammation (CRP and calprotectin) correlate with objective measures of inflammation as detected at VCE. 2. A modified LS (mLS) would be expected to correlate more reliably with biological markers of inflammation than the standard Lewis score. 3. Small bowel transit time negative correlates with the degree of inflammation. Aim: To assess the degree to which small bowel inflammation detected at capsule endoscopy correlates with inflammatory biomarkers and intestinal transit time in patients undergoing VCE. Methods: A retrospective single-centre review of records of consecutive patients attending for VCE between November 2014 and Sept 2016 at a tertiary referral hospital was performed. Data on biomarkers of inflammation processed within 3 months of the VCE were collected. Statistics: The normality of data was assessed using the Shapiro–Wilk test statistic. Correlation was assessed using the Spearman's rank correlation for non-parametric data (2-tailed sig.) Results: VCE data from 286 consecutive patients were collated. Both LS and MLS correlated moderately with faecal calprotectin, with a numerically higher correlation for mLS ( r = 0.379 ( p = 0.032) and r = 0.429 ( p = 0.014), respectively). Neither LS nor mLS showed a significant correlation with CRP ( r = 0.313 ( p = 0.06) and r = 0.277 ( p = 0.096)). LS weakly correlates with small bowel transit time (r = 0.255 ( p = 0.05). Conclusions: Faecal calprotectin, but not CRP correlates with objective assessment of small bowel inflammation as assessed at VCE. A modified Lewis score, incorporating a summation of inflammatory scores for all of three small bowel tertiles more strongly correlates with faecal calprotectin. Small bowel inflammation is associated with a slower small bowel transit time. References: 1. Gralnek et al. Aliment Pharmacol Ther 2008;27:146–54. 2. Kooulaouzidis et al. Ann. Gastroenterol 2015;28:259–264